Development of Augmented Reality–Based Learning Media for Introducing the Concept of Land Animals to Improve the Cognitive Abilities of Early Childhood - Vania, Bunga; Komariyah, Kanada; Ayu, Sovia Mas (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
This research is important to conduct with the aim of producing teaching materials, namely the development of learning media designed in accordance with the age of children, specifically the development of Augmented Reality–based learning media for introducing land animals to improve the cognitive abilities of early childhood. This study employed the Research and Development (R&D) method with the ADDIE development model developed by Dick and Carey. ADDIE stands for Analysis, Design, Development or Production, Implementation or Delivery, and Evaluation. The subjects of this study were 15 students. The research was carried out at TK Thoyyibah Sukarame Bandar Lampung and TK Bangsa Ratu Bandar Lampung. The results showed that this Augmented Reality media was highly valid, as evidenced by the expert evaluations: material experts scored 90%, language experts 75%, and media experts 94%. Furthermore, the trial results at TK Thoyyibah Sukarame Bandar Lampung reached 90.83%, and at TK Bangsa Ratu Bandar Lampung 93.33%. Based on these findings, the Augmented Reality media is deemed feasible for use.